The Relationship between APGAR Score and Delivery Mode with Neonatal Sepsis in Ulin Regional Hospital Banjarmasin - Monica Anggriana Salim; Pricilia Gunawan Halim; Ari Yunanto; Pudji Andayani (Jurnal Kedokteran Brawijaya, 2023)
Neonatal sepsis is one of the most common causes of neonatal death worldwide, affecting up to 3 million neonates each year. Deaths related to neonatal sepsis are more common in developing countries with lower middle incomes. This study aims to find a relationship between APGAR scores at the 1st, 5th, and 10th minutes and delivery mode on the incidence of neonatal sepsis. This research is a retrospective study with a cross-sectional approach at High-Risk Neonatal Installation (INRiT) of Ulin Regional Hospital Banjarmasin, South Kalimantan, conducted from January to December 2022. The total sample was 200 babies divided into the sepsis and the control group. APGAR score data at the 1st, 5th, and 10th minutes and delivery mode were taken through medical records. In this study, the average APGAR score at 1st minute in the sepsis group was 5.11; at 5th minute was 6.56; and at 10th minute was 7.65. The results of APGAR score analysis at the 1st, 5th, and 10th minutes in the sepsis and control groups using the Mann -Whitney test obtained a p-value of 0.000. In the sepsis group, 30 babies were born spontaneously, and 70 babies were born with tools (caesarean section/vacuum extraction). The results of the delivery mode analysis in the sepsis and control groups using Fisher's test obtained a p-value of 0.000 (OR: 3.807) which means that there is a relationship between the APGAR score at the 1st, 5th, and 10th minutes and the delivery mode with the incidence of neonatal sepsis.